Proses Pembelajaran Technological Pedagogical Content Knowladge (TPACK) di Lembaga Dakwah - Faqih, Rizal Al; Sudrajat, Indra (Program Studi Pendidikan Luar Sekolah, 2023)
Abstract This research aims to analyze the process of TPACK (Technological Pedagogical Content Knowledge) learning in a Dakwah Training Institution. TPACK is the integration of technological, pedagogical, and content knowledge that is essential in improving the quality of learning. This study employs a qualitative approach involving observations of the training sessions and interviews with trainers and participants. The training focuses on the integration of TPACK in the learning process at the Dakwah Training Institution.The results of the research indicate that the integration of TPACK provides significant benefits in the development of dai's competencies. Dai can effectively deliver religious messages in the digital era by utilizing innovative teaching strategies such as social media and digital platforms. They also develop relevant technological skills, manage digital content, and utilize online resources. Additionally, the integration of pedagogical knowledge enables dai to implement effective and inclusive teaching strategies. A deep understanding of religious content allows dai to deliver messages with confidence and accuracy. The implementation of TPACK in the Dakwah Training Institution can enhance the quality of religious education. The findings of this research are expected to provide a better understanding of the implementation of TPACK in the context of a Dakwah training institution.Key Words:Â TPACK (Technological Pedagogical Content Knowledge), learning, Dakwah Training Institution.Abstrak Penelitian ini bertujuan untuk menganalisis proses pembelajaran TPACK (Technological Pedagogical Content Knowledge) di Lembaga Pelatihan Dakwah. TPACK adalah gabungan pengetahuan tentang teknologi, pedagogi, dan konten yang penting dalam meningkatkan kualitas pembelajaran. Metode penelitian yang digunakan adalah pendekatan kualitatif, melibatkan pengamatan terhadap pelatihan dan wawancara dengan pelatih dan peserta pelatihan. Penelitian ini fokus pada integrasi TPACK dalam proses pembelajaran di Lembaga Pelatihan Dakwah. Hasil penelitian menunjukkan bahwa integrasi TPACK memberikan manfaat yang signifikan dalam pengembangan kompetensi dai. Dai dapat menyampaikan pesan agama secara efektif dalam era digital dengan menggunakan strategi pembelajaran yang inovatif, seperti media sosial dan platform digital. Mereka juga mengembangkan keterampilan teknologi yang relevan, mengelola konten digital, dan memanfaatkan sumber daya online. Selain itu, integrasi pengetahuan pedagogi memungkinkan dai menerapkan strategi pengajaran yang efektif dan inklusif. Pemahaman yang mendalam tentang konten agama juga memungkinkan dai menyampaikan pesan dengan keyakinan dan akurasi. Implementasi TPACK di Lembaga Pelatihan Dakwah dapat meningkatkan kualitas pembelajaran agama. Hasil penelitian ini diharapkan dapat memberikan pemahaman yang lebih baik tentang implementasi TPACK dalam konteks lembaga pelatihan dakwah.Kata Kunci:Â TPACK, proses pembelajaran, lembaga pelatihan dakwah..